Europa Postmediaevalis 2022 : connections and networking - Blažková, Gabriela, 1974-; Matějková, Kristýna,; Casimiro, Tânia Manuel,; Silva, Ricardo Costeira, (Archaeopress, 2023)
26 contributions divided into five thematic sections consider post-medieval pottery from the perspectives of local, regional and long-distance trade. Papers show the importance of connections and networking and provide an opportunity to compare concrete find situations across Europe - in both coastal as well as landlocked states.